Factors associated with the timely initiation of antenatal care: findings from a cross-sectional study in Northern Bangladesh - Bidhan Krishna Sarker; Musfikur Rahman; Tanjina Rahman; Tawhidur Rahman (BMJ Open)
Objective This paper explored the factors that influence the timely initiation of antenatal care (ANC) in Bangladesh.Design This was a cross-sectional survey.Setting This study conducted in two rural subdistricts and one urban area from three Northern districts of Bangladesh from August to November 2016.Participants Women who had a live birth in the last 1 year prior to data collection were enrolled for this study. In each study area, around 900 women were interviewed, and finally, we completed 2731 interviews.Primary outcome measures The primary outcome was timely first ANC from a Medically Trained Provider (MTP).Results About 43% of pregnancies were detected at their earliest time. The majority of participants (82%) received at least one ANC from an MTP. Only 11% received timely first ANC from an MTP as per the WHO FANC model. The women who detected pregnancy earlier were more likely (adj.OR 1.99, 95% CI 1.31 to 3.01) to receive the timely first ANC. The urban women were more likely (adj.OR 1.78, 95% CI 1.13 to 2.80) to receive the timely first ANC from an MTP than those of the rural women. Besides, their husbands’ educational status (adj.OR 1.61, 95% CI 1.0 to 2.60) was significantly associated with the timely first ANC.Conclusion Apart from sociodemographic factors, early pregnancy detection was strongly associated with the timely first ANC visit. Timely initiation of ANC is an opportunity to adhere to all the WHO recommended timely ANC visits for a pregnant woman. The findings suggest maternal, neonatal, and child health programmes to focus on the early detection of pregnancy to ensure universal ANC coverage and its timeliness.